The Relationship between Interest and Learning Motivation with Physics Learning Outcomes on the Concept of Newton's Laws - Berlian, Ananda Regina; Disha, Lady Pretylia Iraynida; Herman, Netty Berliana; Sabila, Siska Rima; Amalia Putri, Yusinta Dewi; Sudarti, Sudarti; Subiki, Subiki (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This study aims to analyze the effect of student interest and motivation to learn on physics learning outcomes on the concept of Newton's Law. Low interest and motivation to learn is one of the causes of students' difficulty achieving optimal learning outcomes in physics, especially in abstract material such as Newton's Law. The research used a quantitative approach with descriptive statistical methods. Data were obtained through a Likert scale-based questionnaire to measure interest and motivation to learn and a multiple-choice test to assess learning outcomes. Analyses were conducted using multiple linear regression with the help of SPSS. The results showed that interest and motivation to learn significantly influenced student learning outcomes, with a contribution of 73% and a positive relationship. This result confirms the importance of lecturers in designing learning strategies that can increase student interest and motivation to support the success of physics learning, especially in Newton's Law material.